Limberg flap as simplest solution for covering skin defects of different sizes and localizations - Siniša Kojić; Zuhra Memić; Vera Sabljak; Helena Marić Kujundžić; Bojan Kujundžić; Miroslav Obrenović (Биомедицинска истраживања, 2020)
Introduction: Whether it is a classic version of the flap or its modification, the Limberg flap is an appropriate solution for covering small and medium-sized defects, as well as for covering largesized defects where certain localizations are concerned. It represents a local, transposition flap that has proven to be a safe option. Methods: The defect coverage was achieved by marking a defect that was in the form of an equilateral rhombus by means of extending a shorter diagonal by the length of its side and drawing a parallel with the defect side, which created four different flaps. We included 50 patients surgically treated at the Varis Clinic for Plastic and Reconstructive Surgery in Belgrade and the University Hospital in Foca for the period 2018-2020. In all patients, we used the Limberg flap as a method for defect reconstruction. Case presentations. The sample was comprised of up to 50 patients, with an average respondent age of 60.3 years. According to etiology, the most common changes in the skin belonged to Basal cell carcinoma (58%), Squamous cell carcinoma (24%) and melanoma (8%), with the most common predilection sites associated with the face in 22 patients and with the lumbosacral region in 8 patients. A well-planned Limberg flap caused minor complications in terms of mild marginal infection in one patient, and mild marginal infection as an early complication and a stretched scar as a late complication in one patient as well. Other complications in the sample were not recorded. Conclusion: To obtain the best possible functional and esthetic result with minimal disruption of the region, respecting the anatomy and the basic principles in plastic surgery, the Limberg flap is an excellent solution for the reconstruction of defects of different sizes.
Keywords: Limberg flap; local flap; defects; reconstruction